FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN YANG DIMEDIASI OLEH KOMITMEN ORGANISASI PADA ORGANISASI PERANGKAT DAERAH KABUPATEN KAMPAR - Risman, Risman; Kamaliah, Kamaliah (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to analyze the factors that affect the quality of financialreporting with organizational commitment as an Intervening variabel in the localgovernments Kampar. This study population is a civil servant of financial report in theKampar regency with the use of Census methodh with total sample of 84 respondens.The variables used in this study are the Quality of Financial Reporting as dependentvariable and Human Resources Competency, Internal Control System, Utilization ofInformation Technology, and Organizational Commitment as independent variable.sThe analysis tool used is descriptive and qualitative analysis using tools WarpPLS 5 .The result using test coefisient path (Path Coefficient) and value significance (P-value)indicated that the Organizational Commitment, Human Resources Competency and andUtilization of Information Technology have positive and significant inpact diretcly tothe the quality of financial Reporting, but Internal Control System doesnât havesignificant effect. Human Resources Competency and Utilization of InformationTechnology through organizational commitment as an intervening variable havesignificant effects indirectly to the the quality of financial Reporting.